2010
DOI: 10.1111/j.1469-7610.2010.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Population mean scores predict child mental disorder rates: validating SDQ prevalence estimators in Britain

Abstract: Goodman, A; Goodman, R (2010) Population mean scores predict child mental disorder rates: validating SDQ prevalence estimators in Britain. Journal of child psychology and psychiatry, and allied disciplines. ISSN 0021-9630 DOI: 10.1111/j.1469-7610.2010 AbstractBackground: For adult physical and mental health, the population mean predicts the proportion of individuals with "high" scores. This has not previously been investigated for child mental health. It is also unclear how far symptom scores on brief questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(188 citation statements)
references
References 20 publications
5
173
4
6
Order By: Relevance
“…The SDQ has been shown to be reliable and valid in identifying mental health problems. 16,17 Cronbach's Alpha was 0.72 for VP/VLBW (BLS); 0.75 for EP (EPICure); 0.68 for term comparisons (BLS and EPICure).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SDQ has been shown to be reliable and valid in identifying mental health problems. 16,17 Cronbach's Alpha was 0.72 for VP/VLBW (BLS); 0.75 for EP (EPICure); 0.68 for term comparisons (BLS and EPICure).…”
Section: Methodsmentioning
confidence: 99%
“…EPICure: Parents reported on peer bullying in one item of the Strengths and Difficulties Questionnaire (SDQ) 16 ("other children pick on or bully him/her") at both ages. The parents' responses were on a 3-point scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, crosscountry differences in SDQ population means were not supported by the DAWBA individual clinical assessment of study participants. The authors of the SDQ therefore suggested that differences in crosscountry means may not be indicators of differential rates of mental disorders (Goodman & Goodman, 2011), but may rather reflect the lack of populationspecific norms to make 'valid' cross-country comparisons (Goodman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…That is to say that those who are struggling do not form a discrete group (Figure 1), although the proportion with disorder has a linear association with mean symptoms scores (Goodman and Goodman 2011). The level of impairment for any given constellation of difficulties will be influenced by the social and psychological predicament of the individual, something explored in relation to Attention Deficit Hyperactivity Disorder and school context in this issue (Gwernan-Jones et al).…”
Section: Editorial Emotional and Behavioural Difficulties And Mental mentioning
confidence: 99%